CORPORATE CULTURE IN THE CONDITIONS OF TRANSFORMATION: KEY ASPECTS AND FORMATION STRATEGY - VEDERNIKOV, Mykhailo; BAZALIYSKA, Natalia; VOZNIUK, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The world continues to fight the coronavirus pandemic, which has claimed the lives of millions of people around the world. The main measure to prevent the spread of the virus in different countries of the world is the introduction of strict quarantine restrictions, which had a devastating effect on the world economy and stimulated an increase in the number of remote workers. In the new conditions, the study of the development of corporate culture in the mode of remote work becomes relevant. There is no single approach to defining corporate culture in the scientific literature, so we have analyzed several different approaches to this concept.The article analyzes the key aspects of the strategy for forming corporate culture in the context of transformations. The behavioral approach to interpreting the essence of the concept of “corporate culture” in the works of Ukrainian and foreign researchers is presented. The behavioral aspects of forming a corporate culture strategy in the context of transformations of the Ukrainian economy are characterized. The correspondence of the formation of a corporate culture strategy to the general strategy of the enterprise in the context of transformations of the Ukrainian economy is established. The relationship between corporate culture and the competitiveness of the enterprise is shown. A generalized scheme of the influence of corporate culture on the activities of the enterprise is constructed. The features of assessing the effectiveness of corporate culture in the context of economic transformations are determined.The methodological basis of the study is a system of general and special methods, which allowed to investigate the impact of the phenomenon of leadership potential on corporate culture. The study was based on the use of: method of comparison, generalization — to clarify and formalize the essence of the concept; method of correlation and regression analysis — to build multifactor regression models, calculate predictive values of integrated indicators of leadership potential for each subsystem, optimize subsystems, determine the degree of influence on type of corporate culture; graphoanalytical method — to provide clarity of the material and schematic representation of a number of theoretical and practical provisions of the study.
Keywords: corporate culture; corporate culture formation strategy; personnel management; competitiveness; transformation management